Non-pressurized percutaneous endoscopic transforaminal lumbar discectomy in the treatment of cauda equina syndrome caused by lumbar disc herniation - Gao, Shangjv; Shi, Lifang; Cao, Can; Wei, Jingchao; Lv, Wenjie; Li, Wenyi (Frontiers in Surgery, 2025)
ObjectiveCauda equina syndrome (CES) is a rare but devastating condition in spine surgery. There are various surgical decompression methods, but the clinical outcomes are not always satisfactory. We introduce the surgical technique of non-pressurized percutaneous endoscopic transforaminal lumbar discectomy (PETD) technique in the treatment of cauda equina syndrome caused by lumbar disc herniation, and to evaluate its clinical efficacy compared to traditional transforaminal lumbar interbody fusion (TLIF).MethodsA retrospective study was conducted on 51 cases diagnosed with lumbar disc herniation complicated by cauda equina syndrome. They were divided into two groups, 23 cases in the PETD group and 28 cases in the TLIF group. The surgical procedure and technical details of non-pressurized PETD technique were described. Visual analogue scale (VAS) for low back pain and leg pain, Japanese Orthopaedic Association scores (JOA), Oswestry Disability Index (ODI), and the cauda scale (TCS) were used to evaluate the clinical efficacy between the two groups.ResultsThere were no significant differences in baseline data between the two groups. Significant improvements were observed at the final follow-up in both PETD and TLIF groups. The VAS for low back pain and ODI at discharge were lower in the PETD group than those in the TLIF group (both P < 0.05). There were no significant differences in low back pain VAS, leg pain VAS, JOA score, ODI score, and TCS score between the two groups at preoperative and final follow-up. The complications included two cases of intraoperative neck pain and one case of recurrent disc herniation in the PETD group, and one case showed adjacent segment degeneration at the final follow-up in the TLIF group.ConclusionIn this preliminary retrospective study, the non-pressurized PETD technique was associated with similar medium-term outcomes and a faster short-term recovery compared to TLIF. These findings require validation in larger, prospective, randomized controlled trials to establish comparative efficacy.